Maritime Labor Market Demand and Career Path in Latvia - Barbare, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Seafaring profession has traditionally been considered a romantic profession among young people, but in today’s labour market has dramatically changed priorities of career choices. At present, the maritime industry has more than 40 thousand vacancies, in addition to the growing trend - the shipping officers with University level are particularly difficult to recruit for crew shipping companies. The methodology: an analysis of policy documents, statistical data analysis, a secondary analysis of previous research, database analysis, surveys. The motives of choosing profession of young people were determined by economical (good salary, possibility to maintain family welfare, career possibilities and etc.), social (wish to acquire education, seafarers are valuated as specialists, and etc.) and psychological (seafarer’s work seemed to be very interesting, dream to become a captain, and etc.) factors. Both external and internal factors predetermine the choice of seafarer’s profession.The conclusion can be done that maritime education and training institutions have to explain young people all merits of maritime profession and show possibility for them to find emotional attractiveness and realization of their interests if they choose maritime professions.